JUNIOR HIGH SCHOOL STUDENTS’ LIVED EXPERIENCES OF LEARNING ENGLISH USING BUSUU - Vinindita Citrayasa (Indonesian EFL Journal, 2019)
Researches on MALL mostly focus on how learning by using mobile phones gives significant effect on second/ foreign language skills. However, only few which focus on their lived-experiences of learning English using their smart phones anywhere outside their class and anytime outside their school time that can reveal meanings related to their awareness, beliefs, and actions. This research is then aimed at describing and interpreting the students’ lived experience of using a mobile application namely Bussu for learning English. The study is a hermeneutic phenomenology study which focuses on the description and interpretation of the students’ lived experiences of using Busuu to learn English. There were two participants interviewed using in-depth interviews and the data was in the form of texts. The result shows the participants’ lived experiences showed some empirical meanings: ubiquitous learning, fun learning, and useful English learning assistant. This study also reveals the finding of transcendent meaning that Busuu encouraged them to become more autonomous learners.